The Pea R2R3-MYB Gene Family and Its Role in Anthocyanin Biosynthesis in Flowers - Yang, Yating; Yuan, Zhuo; Ning, Conghui; Zhao, Baoling; Wang, Ruoruo; Zheng, Xiaoling; Liu, Yu; Chen, Jianghua; He, Liangliang (Frontiers in Genetics, 2022)
Pea (Pisum sativum L.) is one of the most important legume crops in the world, and it has attracted great attention for its high nutritive values. Recently, the crop breeding program has been focused on the crop metabolic engineering (i.e., color, flavor, nutrition) to improve the quality of crop. As a major group of transcription factors forming the ternary MYB–bHLH–WD repeat protein (MBW) complex to regulate the anthocyanin biosynthesis pathway, members of R2R3-MYB gene family have always been the focus of research targets to improve the valuable metabolic product of crops. Until now, few report about the R2R3-MYB gene family of pea has been released. In this study, we identified 119 R2R3-MYB genes in the assembled pea genome (Version 1a), of which 111 were distributed across 14 chromosomes. Combining with the 126 R2R3-MYB protein sequences of Arabidopsis, we categorized 245 R2R3-MYB proteins into 36 subgroups according to sequence similarity and phylogenetic relationships. There was no member from subgroup 12, 15 and 29 existing in pea genome, whereas three novel subgroups were found in pea and named as N1-N3. Further analyses of conserved domains and Motifs, gene structures, and chromosomal locations showed that the typical R2 and R3 domains were present across all R2R3-MYB proteins, and Motif 1, 2, and 3 were identified in most members. Most of them had no more than two introns. Additionally, 119 pea R2R3-MYB genes did not experience large-scale duplication events. Finally, we concluded that several candidate genes may be responsible for the spatiotemporal accumulation of anthocyanins in pea petals. PsMYB116 was predominantly expressed in the dorsal petals to presumably activate the anthocyanin biosynthesis pathway, while PsMYB37 and PsMYB32 may positively regulates the anthocyanin accumulation in the lateral petals. This study not only provides a good reference to further characterize the diverse functions of R2R3-MYB genes but also helps researchers to understand the color formation of pea flowers.